Diversity Patterns and Composition of Native and Exotic Floras in Central Chile - Castro-Morales, S (2011)
Floristic changes in the Mediterranean region of central Chile brought about by human impact appear to be shared with other climatic regions, although there is a notable absence of empirical studies and available quantitative evidence for the central Chile region. This study examines the cover, richness and composition of native and exotic plant species in a representative area of central Chile. Through floristic characterization of 33 sites sampled using 40 × 40 m plots distributed along transect on which the two farthest sites were separated by 50. km, the floristic richness and cover patterns, as well as the general land use characteristics were evaluated (native matorral, espinal, abandoned farming field, forest plantations, periurban sites, road sites, river bank, and burnt site). We recorded 327 species of plants; 213 species were native and 114 were exotic. The average number of species was heterogeneous in all sites, showing a greater relative native frequency in those sites with a lower level of anthropic intervention. Except for the matorral, the cover of exotic species was greater than that of native species. No relation was found between richness and cover in relation to the different types of land use. The relationship between cover of native and exotic was negative, although for richness did not show relationship. Results show that the exotic species are limited by resources, although they have not completely displaced the native species. The native and exotic floras respond to different spatial distribution patterns, so their presence makes it possible to establish two facts rarely quantified in central Chile: first, that the exotic flora replaces (but does not necessarily displace) the native flora, and second, that at the same time, because of its greater geographic ubiquity and the abundance levels that it achieves, it contributes to the taxonomic and physiognomic homogenization of central Chile. © 2011 Elsevier Masson SAS.